Change and convergence of income distributions in the European Union during 2007-2014 - Zsombor Cseres-Gergely; Virmantas Kvedaras (Publications Office of the European Union, 2019)
Mainstream monitoring of income dynamics and inequality is based on summary measures that can miss important phenomena prevalent in income distributions. Relying on quantile functions and the adapted statistical framework suggested by Szekely and Rizzo (2004), we characterize the change and convergence of net equivalized income distributions among European Union countries. We exploit the scale-independence property of proper inequality metrics to evaluate not only the total but also the inequality-affecting (shape-influenced) convergence of distributions.
Keywords: D31; D63; O15; 330; convergence; European Union; income distribution; inequality